Photonic Generation of Multilevel Frequency-Hopping Microwave Signal - Xia Feng; Lianshan Yan; Hengyun Jiang; Peng Li; Jia Ye; Yin Zhou; Wei Pan; Bin Luo; Xihua Zou; Tao Zhou (IEEE Photonics Journal, 2019)
A photonic scheme to generate a 4-level frequency hopping (FH) microwave signal is proposed and experimentally demonstrated. The frequency of the generated signal can be fast and flexibly switched by shifting the combinations of two binary signals (i.e., 00, 01, 11, 10). Moreover, the carrier frequencies of the signal can be tuned in a large range. In the experiments, 2/4/6/12, 4/6/8/12, and 6/9/12/18 GHz FH signals are generated with the FH speed up to gigahertz.